THE EFFECT OF TABOO WORD GAME IN IMPROVING VOCABULARY ABILITY - Reni Rosianna Lumbangaol (Universitas Potensi Utama, 2021)
This study was conducted to investigate the effect of Taboo Word Game strategy on students vocabulary ability. The purpose of the study was to find out the effect of Taboo Word Game strategy had effect on students’ vocabulary ability. The study used research by doing experimental design. The population of this study was 60 Informatics Engineering students of Potensi Utama University in the fourth semester of 2019-2020 Academic Year. A placement test was given to 60 students. 60 students were taken as the sample of this research. The sample was divided into two groups: the first group is the Taboo Word Game group (30 students) and the second group is conventional group (30 students). The instrument of collecting the data was vocabulary test. The writer used independent sample t test formula to analyse the data. The data were calculate by using independent sample t test by SPSS 20 for windows. The result of the analysis shows that tcount > ttable = 3,941 < 2,66329 is higher at the level of significance 0.05 and the degree of freedom (df) 58. Therefore, the null hypothesis (Ho) is rejected the alternative hypothesis (Ha) is accepted.